The Influence of Organizational Activeness and Time Management on Students' Communication Ability - Choirunisa, Mila Mutiara; Madjid, Abd (CV. Creative Tugu Pena, 2023)
The aim of the research is: 1) to prove the influence of organizational activeness towards the communication ability, 2) to prove the influence of time management towards the communication ability, and 3) to prove the influence of organizational activeness and time management simultaneously towards the communication ability. The research implemented quantitative approach. The population of the research was students who were active in organization of Islamic Education in Universitas Muhammadiyah Yogyakarta from batch 2020 and batch 2021, consisting of 93 students. The data collection was done using questionnaire with Likert scale. The data analysis was done using descriptive statistic and multiple regression analysis to test the hypothesis. The results of the research are as follows: 1) Organizational activeness gives partial influence and has positive influence towards the communication ability of Islamic Education students from batch 2020 and batch 2021 Universitas Muhammadiyah Yogyakarta. 2) Time management gives partial influence and has positive influence towards the communication ability of Islamic Education students batch 2020 and batch 2021 Universitas Muhammadiyah Yogyakarta. 3) The organizational activeness and time management gives simultaneous influence towards the communication ability of Islamic Education students from batch 2020 and batch 2021 Universitas Muhammadiyah Yogyakarta. Moreover, the amount of influence of organizational activeness and time management towards the communication ability of Islamic Education students from batch 2020 and batch 2021 Universitas Muhammadiyah Yogyakarta is 53.7%. Keywords: : Organizational Activeness, Time Management, Communication Ability